Olhares que fazem a diferença: o índio em livros didáticos e outros artefatos culturais - Teresinha Oliveira Silva de (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2003)
The text discusses how Indians are presented as distinct based on ways of looking as materialised in textbooks, stamps and postcards, etc. marking the pedagogical function of apparently banal artefacts. The article is divided into three thematic segments: the first is related to the diverse ways in which the other is seen, the second, to the transposition of meanings attributed to objects and the third discusses the representation of Indians by means of postcards, phonecards and national coins, as authentic Brazilians and patrimony of the nation. The framework that supports this approach is related to the field of cultural studies in a post-modern perspective. In this sense, the concepts articulated in these productions were analysed as a set of established discursive practices based on relations of power.